Jack of Fables. [9], The end - Willingham, Bill (DC Comics, 2011)
Jack Frost has just set upon the greatest quest in a long and distinguished career of great quests, to kill a dragon. Of course, he is not aware that the dragon in question is in fact his own father. Meanwhile, the Page Sisters find a new purpose in life, restoring the Great Library. This volume includes Jack of fables #50, a special issue that includes appearances by everyone who has ever shown up in the series.